Re(I) and Tc(I) Complexes for Targeting Nitric Oxide Synthase: Influence of the Chelator in the Affinity for the Enzyme. (7th May 2015) - Oliveira, Bruno L.; Morais, Maurício; Mendes, Filipa; Moreira, Irina S.; Cordeiro, Carlos; Fernandes, Pedro A.; Ramos, Maria J.; Alberto, Roger; Santos, Isabel; Correia, João D. G.
Abstract : Aiming to design 99m Tc complexes for probing nitric oxide synthase (NOS) by SPECT, we synthesized conjugates (L4 –L6 ) comprising a NOS‐recognizing moiety connected to a diamino‐propionic acid (dap) chelating unit. The conjugates led to complexes of the type fac ‐[M(CO)3 (ĸ 3 ‐L)] (M = Re/ 99m Tc;Re4 /Tc4 : L = L4 ;Re5 /Tc5 : L = L5 ;Re6 /Tc6 : L = L6 ). Enzymatic studies showed thatL4 andL5, but notL6, gave complexes (Re4 andRe5 ) that are less potent than the conjugates. To rationalize these results, we performed docking and molecular dynamics simulations. The high affinity ofL4 andL5 is due to the strong interactions between the dap chelator and polar residues of the binding cavity. These interactions are hampered by metallation resulting in complexes with lower affinity. The higher potency ofRe5 compared toRe4 was assigned to the increased bulkiness ofRe5 and the presence of additional anchoring groups that better fit the active site and provide more extensive contacts. In turn, Re6 is too bulky and its organometallic tail is oriented toward the peripheral pocket of iNOS, leading to loss of contacts and a lower affinity. These results were compared with our previous results obtained with analogue complexes stabilized by a pyrazolyl‐diamine chelating unit. Abstract : Molecular dynamics simulations suggested that the high affinity ofL4 andL5 for iNOS is due to strong interactions among the NH3 + and CO 2 − groups of the chelator and the polar residues of the binding cavity, which are hampered by metallation. The higher inhibitory potency ofRe5 compared toRe4 was assigned to the increased bulkiness of its organometallic tail and the presence of additional anchoring groups. The organometallic tail ofRe6 is not accommodated within the binding pocket of iNOS.